2016
DOI: 10.1021/acs.jnatprod.5b00987
|View full text |Cite
|
Sign up to set email alerts
|

A Grand Challenge: Unbiased Phenotypic Function of Metabolites from Jaspis splendens against Parkinson’s Disease

Abstract: A grand challenge in natural product chemistry is to determine the biological effects of all natural products. A phenotypic approach is frequently used for determining the activity of a compound and its potential impact on a disease state. Chemical investigation of a specimen of Jaspis splendens collected from the Great Barrier Reef resulted in the isolation of a new pterin derivative, jaspterin (1), a new bisindole alkaloid, splendamide (2), and a new imidazole alkaloid, jaspnin A (3) TFA salt. Jaspamycin (8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…Additionally compound 917 contains the rare indole-3-carboximidamide motif. 444 Each year the vast majority of sponge-derived compounds fall into the isoprenoid class and 2016 was no exception. A specimen of Spongia yielded two merosesquiterpenoids 918 and 919 (ref.…”
Section: Spongesmentioning
confidence: 99%
“…Additionally compound 917 contains the rare indole-3-carboximidamide motif. 444 Each year the vast majority of sponge-derived compounds fall into the isoprenoid class and 2016 was no exception. A specimen of Spongia yielded two merosesquiterpenoids 918 and 919 (ref.…”
Section: Spongesmentioning
confidence: 99%
“…26 Jaspamycin 22had the highest deviation from control over the 38 biological parameters in the unbiassed hONS cell phenotypic assay out of the 22 secondary metabolites isolated from Jaspis splendens. 27 Subsequent target identification is required for molecules that have cellular activity.…”
Section: Esther Kellenbergermentioning
confidence: 99%
“…The data included compounds with known mechanism of action so that phenotypic data may subsequently lead to the discovery of particular targets. 27,48,49 We used the cytological parameters followed by hierarchical clustering and vizualisation as a dendogram. 27,48,49 AI can treat each data point separately.…”
Section: Data Set 6 Phenotypic Cellular Activitymentioning
confidence: 99%
“…The first screen covered isolated metabolites from marine sponges (Jaspis splendens) to prove that the overall system could function. The following screen then utilized a 500-plus pure compound set from the Nature Bank collection at Griffith University [1,4,29,30]. The results demonstrated that such a HCS produced multiple possibilities for the identification of the interaction(s) with cellular organelles/protein interactions, being limited only by the specificity of the fluorescent probes used to demonstrate the responses.…”
Section: Application Examples Of Hcs In Natural Product Researchmentioning
confidence: 99%